Structural lightweight aggregate concrete exposed to marine environment for 5 years. (15th March 2021) - Real, Sofia; Bogas, José Alexandre; Pontes, Jorge
Highlights: Structural lightweight aggregate concrete was exposed to marine environment for 5 years. Chloride penetration into structural lightweight aggregate concrete was characterised. Structural lightweight aggregate concrete can have the same durability as common concrete. The surface chloride content was higher in structural lightweight aggregate concrete. The estimated chloride profiles from existing models did not fit the real results. Abstract: The present paper characterises the chloride penetration into a large array of structural lightweight aggregate concrete (LWAC), after a 5-year exposure period to aggressive marine conditions. The chloride profiles, chloride diffusion coefficients and surface chloride contents were determined and the influence of the main composition parameters and exposure conditions was assessed. Current service life models were evaluated through the estimation of chloride profiles. The results suggest that LWAC can present the same durability as normal weight concrete (NWAC). However, despite having the same chloride diffusion coefficients, the surface chloride content of LWAC tended to be greater than that of NWAC, leading to higher chloride penetration at a given depth. In general, the estimated chloride profiles from existing models did not fit the real results.